Total Anonychia Congenita with Carpal Synostosis - Milad Bahari; Negar Douzandeh (Disease and Diagnosis)
Background: Anonychia congenita is a rare genetic disorder of fingernails and/or toenails with unknown prevalence leading to aplasia of nail structures which may be seen either as an isolated abnormality or as part of a syndrome affecting multiple parts of the body such as nail-patella syndrome. In some cases, not all fingers or toes are involved or only part of the nail is absent (hyponychia). Case Report: A 36-year-old man with the absence of all fingernails and toenails of both hands and feet was presented in this study. The patient claimed that his anomaly was present at birth. He had normal developmental milestones and normal intelligence. The patient’s general medical history was unremarkable. His parents were first-degree cousins and were completely healthy and unaffected. All his brothers and sisters were also unaffected. There were no co-existing symptoms except obvious signs of synostosis between trapezoid and trapezium bones detected bilaterally in both hands and unilateral capitate-hamate synostosis found in the right hand in radiographic assessment. Conclusion: The patient was diagnosed with total congenital anonychia accompanied by bilateral carpal synostosis. Genetic analysis is warranted to confirm the diagnosis and identify the causative gene in this case.